The Use of Artificial Intelligence for Primary School Mathematics: A Bibliometric Analysis - Salido, Achmad; Haryanto; Kenedi, Ary Kiswanto; Agustiana Putri , Dya Ayu (Faculty of Teacher Training and Education, Universitas Terbuka, 2024)
The role of technology, particularly artificial intelligence, in the increasingly advanced digital age has the potential to revolutionize the educational landscape in unprecedented ways. This study aims to analyze and elucidate trends related to the utilization of artificial intelligence in mathematics activities within primary schools, as well as to uncover potential research opportunities for the future. Articles for this study were retrieved from the Scopus database using the search string